Low wnt/β-catenin signaling determines leaky vessels in the subfornical organ and affects water homeostasis in mice - Fabienne Benz; Viraya Wichitnaowarat; Martin Lehmann; Raoul FV Germano; Diana Mihova; Jadranka Macas; Ralf H Adams; M Mark Taketo; Karl-Heinz Plate; Sylvaine Guérit; Benoit Vanhollebeke; Stefan Liebner (eLife, 2019)
The circumventricular organs (CVOs) in the central nervous system (CNS) lack a vascular blood-brain barrier (BBB), creating communication sites for sensory or secretory neurons, involved in body homeostasis. Wnt/β-catenin signaling is essential for BBB development and maintenance in endothelial cells (ECs) in most CNS vessels. Here we show that in mouse development, as well as in adult mouse and zebrafish, CVO ECs rendered Wnt-reporter negative, suggesting low level pathway activity. Characterization of the subfornical organ (SFO) vasculature revealed heterogenous claudin-5 (Cldn5) and Plvap/Meca32 expression indicative for tight and leaky vessels, respectively. Dominant, EC-specific β-catenin transcription in mice, converted phenotypically leaky into BBB-like vessels, by augmenting Cldn5+vessels, stabilizing junctions and by reducing Plvap/Meca32+ and fenestrated vessels, resulting in decreased tracer permeability. Endothelial tightening augmented neuronal activity in the SFO of water restricted mice. Hence, regulating the SFO vessel barrier may influence neuronal function in the context of water homeostasis.